2022
DOI: 10.1038/s41581-022-00538-3
|View full text |Cite
|
Sign up to set email alerts
|

The evolving story of apolipoprotein L1 nephropathy: the end of the beginning

Abstract: Genetic coding variants in APOL1 , which encodes apolipoprotein L1 (APOL1), were identified in 2010 and are relatively common among individuals of sub-Saharan African ancestry. Approximately 13% of African Americans carry two APOL1 risk alleles. These variants, termed G1 and G2, are a frequent cause of kidney disease — termed APOL1 nephropathy — that typically manifests as focal segmental glomerulosclerosis and the clinical syndrome of hypertension and arterionephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 148 publications
(195 reference statements)
1
48
1
3
Order By: Relevance
“…There is correlation between the prevalence of hypertension and the zones of APOL1 genetic risk variant distribution in Africa [16]. It is no longer in doubt whether APOL1 risk variants are susceptibility factors to non-diabetic CKD as it has been reported across many studies and we have also shown the same results in the Cameroonian population [17]. What remains yet to be established is a causal relationship between the APOL1 variants and non-diabetic CKD.…”
Section: Discussionsupporting
confidence: 77%
“…There is correlation between the prevalence of hypertension and the zones of APOL1 genetic risk variant distribution in Africa [16]. It is no longer in doubt whether APOL1 risk variants are susceptibility factors to non-diabetic CKD as it has been reported across many studies and we have also shown the same results in the Cameroonian population [17]. What remains yet to be established is a causal relationship between the APOL1 variants and non-diabetic CKD.…”
Section: Discussionsupporting
confidence: 77%
“…Reports indicate that a history of amputation or ulceration, 68 peripheral edema, 69 foot pressure, 70 plantar callus formation, 71 nephropathy, 72 poor glucose control, 73 ischemia, 74 retinopathy 75 and prolonged diabetes 76 is an important predisposing factor leading to the development of DFUs. Recent studies have reported that diabetic wounds exhibit a prolonged inflammatory phase due to impairment of phagocytes and macrophages, resulting in the excessive release of MMPs (matrix metalloproteinases), causing degradation of collagen and extracellular matrix (ECM).…”
Section: Pathophysiology Of Diabetic Foot Ulcers (Dfus)mentioning
confidence: 99%
“…However, most people with APOL1 kidney-risk genotypes, including those with HIV, do not develop CKD, suggesting other genetic or environmental factors are likely to be required. The best recognized are immunodeficiency, HIV viraemia and hepatitis C co-infection or other infections such as parvovirus B-19 and coronavirus disease 2019 (COVID-19) which result in interferon-mediated activation of the APOL1 promoter, although most individuals with APOL1 nephropathy do not have an obvious cofactor [36 ▪▪ ].…”
Section: Host Factors Implicated In the Development And/or Progressio...mentioning
confidence: 99%